Geopolitical concepts: definition and importance - Proroković, Dušan (Napredak, 2025)
In practical terms, geopolitics is manifested through geopolitical concepts. These concepts are strategic perceptions based on geographical (socio-geographical and physical-geographical) and political indicators relevant for shaping certain goals. This paper explains the definition and importance of geopolitical concepts, as well as the necessary conditions for their legitimization. In that context, to understand certain geopolitical concepts (i.e., to understand the constants on which concepts are based), it is necessary to know the long-standing historical processes which also form collective strategic perceptions. Illegitimate geopolitical concepts cannot be successful, nor can they last in time, which is essentially opposite to the objectives of geopolitics. That is why a conclusion is imposed that successful geopolitics may not be based on any ad hoc actions, but they imply strategic deliberation, long-term planning and a multidisciplinary approach in ensuring interests of the state and the nation creating the state.